THE INFLUENCE OF BRAND AMBASSADOR, BRAND PERSONALITY, AND KOREAN WAVE ON PURCHASE DECISIONS OF SOMETHINC - Rona Ayudia Purnandika; Mohamad Trio Febriyantoro; Zulkifli Zulkifli; Dede Suleman; Fendi Saputra; Yohanes Totok Suyoto (Asosiasi Dosen Muda Indonesia, 2022)
This study aims to determine the influence of Brand Ambassadors, Brand Personality and the Korean Wave on the Purchase Decision of somethinc products. This research is research that uses quantitative data. The population of this research is so-think consumers. The sample in this study amounted to 120 respondents. The techniques used are validity test, reliability test, classic assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis, F test, and T test. The results of this study indicate that Brand Ambassador and Brand Personality simultaneously significantly affect purchasing decisions. Meanwhile, the Korean Wave simultaneously has no significant effect on purchasing decisions of something. Brand Ambassador has a positive and significant effect on purchasing decisions, Brand Personality has a positive and significant effect on purchasing decisions, and Korean Wave has a negative and insignificant effect on purchasing decisions.